Information technology for management : Federated Conference on Computer Science and Information Systems, ISM 2015 and AITM 2015, Lodz, Poland, September 2015, revised selected papers /: Federated Conference on Computer Science and Information Systems, ISM 2015 and AITM 2015, Lodz, Poland, September 2015, revised selected papers. (2016) - Unknown
No abstract available